2015
DOI: 10.3109/10253890.2015.1117449
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrollable and unpredictable stress interacts with subclinical depression and anxiety scores in determining anxiety response

Abstract: According to learned helplessness theory, uncontrollable stress is assumed to be a critical etiological factor in the pathogenesis of depression. In contrast, unpredictability of stressors is assumed to facilitate the development of sustained anxiety. Despite the frequent co-morbidity of depression and anxiety disorders, these two factors have rarely been studied simultaneously in humans. Therefore, we investigated whether there are interaction effects of uncontrollability and unpredictability on anxiety respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…Fifty years of research more thoroughly investigating this finding revealed that animals showed symptoms of greater passivity, reduced social interaction, neophobia, and decreased food intake in response to inescapable stress [2]-behaviours mirrored in the symptoms of anxiety and depression in humans [3]. Indeed, studies in humans linked the lack of control over a stressor with increased subjective stress [7], anxiety [8], pain intensity perception [9], deficits in selective attention [10], and impaired fear extinction learning [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty years of research more thoroughly investigating this finding revealed that animals showed symptoms of greater passivity, reduced social interaction, neophobia, and decreased food intake in response to inescapable stress [2]-behaviours mirrored in the symptoms of anxiety and depression in humans [3]. Indeed, studies in humans linked the lack of control over a stressor with increased subjective stress [7], anxiety [8], pain intensity perception [9], deficits in selective attention [10], and impaired fear extinction learning [11].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas animal research can boast established, well-standardised paradigms [5], human studies are largely heterogeneous concerning their experimental setup and the outcome variables they investigate. To illustrate this, stressors ranged from physical stimuli, i.e., electric shocks [8,9,11], thermal stimulation [20], and loud sounds [7,10] to video clips of snakes [19] and unsolvable reasoning tasks [21]. Probably for reasons of feasibility, many studies opted for a within-subject design, rather than comparing three groups according to the triadic design.…”
Section: Introductionmentioning
confidence: 99%
“…The model also suggests that current life stress interacts with dispositional vulnerabilities and can further aggravate suicidal ideation. We included these interactions in our adaptation of the model and treat somatic symptom severity and anxiety as the main stress‐relevant indicators of cardiac patients (Edmondson, Newman, Whang, & Davidson, ; Havranek et al, ; Niérat, Laviolette, Hudson, Similowski, & Sévoz‐Couche, ). Moreover, we hypothesize that a history of myocardial infarction, together with severe somatic symptoms, may trigger suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results point rather to a tendency towards a lower probability of receiving a diagnosis of anxiety in obligate carriers of a severe CYP21A2 mutation. Unpredictable psychological stressors are more likely to result in depressive symptoms than predictable stressors . Is it possible that the exaggerated increase in the ACTH response is of greater importance than a smaller increase in CRH over time.…”
Section: Discussionmentioning
confidence: 99%
“…Unpredictable psychological stressors are more likely to result in depressive symptoms than predictable stressors. 26 Is it possible that the exaggerated increase in the ACTH response is of greater importance than a smaller increase in CRH over time.…”
Section: Discussionmentioning
confidence: 99%